An attempt to identify the needs of visitors to the Warsaw - Mirecka, Anna (Studia Ecologiae et Bioethicae, 2016)
This article reviews research conducted in Warsaw’s Zoological Garden. The aim of the research was to define behavior and reactions of visitors. Examination was carried out on selected exhibitions: elephants, gorillas, jaguars, donkeys, and goats (3 newly-built and one traditional). 25 separate category of behaviors and reactions of visitors were evaluated in five social groups: F (female), F+Ch (female+child), M (male), M+Ch (male+child), and Ch (child). Behaviors and reactions were recorded in ordinal scale 0-1, and the total number of points revealed the most frequent behaviors and reactions. The results of this research indicate that there is a correlation among some behaviors and reactions, arrangement of exhibitions as well as a time of observation of displays. Another important finding was that the arrangement and the service had a great significance for increasing the attractiveness as well as educational value of an exhibition. The most interesting finding was that visitors watching modern naturalistic exhibits were making photographs of them even if the animals were hidden from their view. In general, therefore, it seems that modern naturalistic settings of animal exhibits are clearly more attractive for visitors than traditional ones.